Improving potassium use efficiency of sugarcane through the use of polyhalite - Wilfrand Ferney Bejarano Herrera; Bruna Arruda; Hudson Wallace Pereira de Carvalho; Paulo Sergio Pavinato (CABI Agriculture and Bioscience)
Abstract Background Sugarcane (Saccharum officinarum) is an important crop in the production of food and energy in tropical and subtropical regions. To provide plants with what they need, highly concentrated fertilizers are often deployed which can result in imbalances in plant nutrition. The purpose of this study was to assess the efficiency of polyhalite (K2Ca2Mg(SO4)4·2H2O) as an alternative source of multinutrients for sugarcane compared to single sources of K, Ca, Mg and S. Methods A glasshouse experiment was carried out on a low-K Entisol from the sugarcane cultivar CV7870. A completely randomized design was used with different K fertilizer management strategies as follows: four K dosages (0, 21, 42 and 63 mg dm−3) associated to distinct sources, namely: polyhalite (PHY); potassium chloride (KCl); potassium chloride+polyhalite in a 1:1 ratio (½KP), and potassium chloride combined with phosphogypsum and kieserite balancing Ca, Mg and S dosages as supplied by pure polyhalite (KGK). Two growth cycles in 6 dm3 soil pots were evaluated: cane plant harvested at 131 days after transplanting, and ratoon harvested at 253 days after transplanting for the determination of dry matter production. Immediately before harvesting in both cycles, leaf nutrient content (K, Ca, S and Cl) was determined using a hand-held X-ray fluorescence spectrometer. Results In general, shoot dry matter and nutrient uptake were higher with the highest K dosage applied and K sources containing Ca and S in the formulation PHY; ½KP; and KGK, for both growth cycles. However, when these sources were provided at the lowest dosage, high agronomic efficiency was observed in all nutrients assessed. Consequently, the cultivar CV7870 was responsive to K application. However, increments in the K dosage resulted in low agronomic efficiency. Conclusions This study indicates that PHY is an effective fertilizer for sugarcane farmers seeking to improve nutrient uptake in a low-K Entisol for both cane plant and ratoon. A mix of PHY and KCl is a potential multi-nutrient fertilizer for managing sugarcane production.